Pengembangan Aplikasi Frontdesk Berbasis Web (Studi Kasus : LPPM UB) - Mohammad Alfan Iqbal Aknaf; Welly Purnomo; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Institute of Research and Community Services (LPPM) Brawijaya University is a unit that carries out the main tasks and functions of Brawijaya University in the sector of research and community service. In carrying out their duties, LPPM leaders are assisted by a secretary. The several tasks of the secretary are events scheduling, loan room scheduling, and leader's appointment scheduling. During this time the task is still done manually, now the solution that is applied is still using excel files and google calendar service, so there is no integration between one data with the other data, while the three scheduling data have relationship with each other. Based on these problems the frontdesk application was made which can be used by secretary and receptionist of LPPM to serve event scheduling, loan room scheduling, and leaders appointment scheduling. Furthermore, to test the implementation result of the making event schedule, making loan room schedule, and making leaders appointment function, validation and user acceptance testing were performed. From the testing phase, the result obtained 74.88% which indicates thet the application built can help users in recording scheduling data and also the application can be accepted and approved by the user.